Fulfillment of the Food Needs of the Community Around the Forest Area with the Agroforestry System at RPH Mundu - Sulastri, Sri; Zairina, Anisa; Widyastuti, Diena; Putra, Angganata Rona Syah (Universitas Muhammadiyah Sidoarjo, 2022)
The success of forestry development through agroforestry activities is largely determined by the level of community participation in contributing to forest management efforts and the quality of human resources that support it. In order to realize the success of RPH Mundu, the community forest management program (PHBM) is carried out. The principle of PHBM is to open opportunities and opportunities for all parties to manage forests with a sharing system while maintaining forest sustainability. The paradigm shift in forest management demands a change in attitudes, work procedures and institutional structures related to the implementation of the CBFM system. The method used in this research is a survey method and direct observation in the field. Sampling of the success of agroforestry development at RPH Mundu was based on the type of vegetation, the amount of vegetation, the height and diameter of the main production plant/polowijo/hectare, production costs, B/C ratio. Determination of respondents for communities around the forest intentionally or purposive sampling, namely 67 respondents who are members of the forest farmer group (KTH). Sampling was selected based on age, duration, number of families and based on the area arable. Based on the results of the analysis, the fulfillment of the food needs of the community around the forest area with the agroforestry system at the Mundu RPH is quite good and feasible to continue its use. Fulfillment of community food needs includes three aspects, namely: adequacy aspect, health aspect and nutritional content aspect.